The host background of rice influences the resistance expression of a three genes pyramid (xa5 + xa13 + Xa21) to bacterial blight (Xanthomonas oryzae pv. oryzae) pathotypes of Indian mainland and Bay islands. (28th March 2017) - Sakthivel, Krishnan; Gautam, Raj K.; Manigundan, Kaari; Singh, Reena; Ramalingam, Jegadeesan; Laha, Gouri S.; Kumar, Aundy; Velazhahan, Rethinasamy
Abstract: Bacterial blight (BB) is a major disease of rice for which host resistance is the only effective solution. The three genes pyramid xa 5  + xa 13  + Xa 21 is recently the most utilized combination for developing resistant varieties through marker‐assisted breeding. Our study was carried out to elicit the detailed response of twenty lines possessing these three genes in five genetic backgrounds to twelve diverse BB pathotypes in India. The lines developed from ADT 47 variety showed incomplete resistance to most of the pathotypes, whereas susceptibility varied from 8.3% to 16.6% in ADT 43 and IR24, respectively. However, in IMP ASD16/60 and Improved Samba Mahsuri, complete resistance against all pathotypes was observed. The overall results confirmed that genetic background plays crucial role for the effective expression of xa 5  + xa 13  + Xa 21 combination. Molecular studies did not reveal correlation between origin of pathotypes and their virulence potential. It is suggested to deploy Improved Samba Mahsuri, IMP ASD 16/60 and AD1306 varieties in the bacterial blight prone areas or use them as donors for realizing wider and durable resistance.